Research of the status of scientific and technical development of the countries of the world - Reshetnyak, Olena (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
In modern conditions to ensure sustainable economic growth of the country and increase the competitiveness of the national economy, it is necessary to ensure scientific and technological development. The purpose of the article is to study the state of scientific and technical development of the countries of the world in the context of developing recommendations for Ukraine. Method of research: graphical and statistical analysis of indicators of scientific and technical activity, index method for calculating the integral indicator of scientific and technical activity of the country. The work analyzed the dynamics of the main indicators characterizing the scientific and technical activity. In order to identify the leader among the countries in the scientific and technological development, the calculation of the integral indicator, which determines the place of the country in the overall ranking of countries, was calculated. According to the results of the calculation - the best result is demonstrated by the USA, and Ukraine is the last among the estimated countries. It is proved that the current state of scientific and technological activity in Ukraine does not correspond to its orientation towards sustainable and innovative development, which are declared in the relevant strategic documents. The USA’s success in providing innovative development has been analyzed in order to develop recommendations for improving the scientific and technical state of Ukraine. It is determined that in the USA the promotion of scientific and technological activity is conditioned by the implementation in the country of a new model of the national innovation system is the model of a triple spiral. Conclusions: the study of the experience of scientific and technical activity of different countries of the world gives Ukraine the opportunity to formulate its own priorities for development in this sphere, which will ensure the formation of an innovative economy.